Keanekaragaman Gastropoda di Sungai Gembolo, Kecamatan Pungging, Kabupaten Mojokerto - Nafilah Zerlita Fahrani; Reni Ambarwati; Dwi Anggorowati Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the gastropod diversity in the Gembolo River, Pungging District, Mojokerto Regency. The sampling method used was manual collection (hand picking) at three observation stations, and species identification was conducted based on morphological characteristics. The results showed that five gastropod species belonging to four families were found in the Gembolo River. The diversity index value of 1.06 indicates a moderate level of diversity. The dominance index value of 0.42 suggests that no single species dominates the gastropod community. In conclusion, the gastropod diversity in the Gembolo River is categorized as moderate, with no dominant species observed. Keywords: Biodiversity, Gastropods, Freshwater Snails, Morphometry